2013
DOI: 10.14233/ajchem.2013.14515
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Ion Association of s-Acetylthiocholine Halides and Perchlorate in Acetonitrile

Abstract: Thermodynamic parameters (∆Hº, ∆Gº, ∆Sº) and the activation energy (∆Es) were calculated to explain the limiting equivalent conductance (Λ0) and ion association constant (KA) of s-acetylthiocholine halides and perchlorate in acetonitrile at different temperatures by using conductance measurements. It has been evaluated by using Fuoss-Onsager equation. It is evident that the values of (Λ0) increase regularly with increase in temperature. For all salts of s-acetylthiocholine, (Λ0) indicates less solvation or hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…El-Hammamy et al [2][3][4][5][6]8 , measured the conductances of Sacetylthiocholine halides and perchlorate in methanol, ethanol, n-prpanol, n-butanol, 2-propanol and acetonitrile solutions at 25 ºC. They found that the same trends of solvation (aº) for all organic solvents are in agreement with the present results.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…El-Hammamy et al [2][3][4][5][6]8 , measured the conductances of Sacetylthiocholine halides and perchlorate in methanol, ethanol, n-prpanol, n-butanol, 2-propanol and acetonitrile solutions at 25 ºC. They found that the same trends of solvation (aº) for all organic solvents are in agreement with the present results.…”
Section: Resultssupporting
confidence: 87%
“…The solvation (aº) in Table-4 increases with increased the temperature from (35-40 ºC) for salts of S-acetylthiocholine Brto ClO4 -. The same results were obtained for these salts in ethanol 13 and acetonitrile at different temperatures from (30-35 ºC) 14 .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…They expound the scattering of the points and difference between the (ri intercept) and (ri slope) values to certain specific parameters such as solvation which are neglected in the continuum model and these show a very important role in determining mobility of ions. El-Hammamy et al [8], calculated the hydrated radii and hydrodynamic radii for acetylcholine ion and ClO and s-alkylisothiouronuim ions (s-Meis + , s-n-Buis + , sn-Amis + and s-n-Heptis + ) in water, methanol, n-propanol and CH3CN at 25°C. They found that the radii obtained from the slope increase with increase in size for both cation and anions.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of this approach, the structure modification of the water takes place by the addition of an acid. Such an influence has been investigated by conductance measurements for S-acetylthiocholine halides and perchlorates in methanol solution 9 . Many investigations have been carried out in aqueous solution catalyzed by both acid and base [10][11][12] (1) The mechanisms of many acid and base-catalyzed reactions have been established using kinetic data in order to measure the reaction rate in a wide range of acid or base concentrations 13 .…”
Section: Introductionmentioning
confidence: 99%